2023
DOI: 10.1002/anie.202300685
|View full text |Cite
|
Sign up to set email alerts
|

Regio‐ and Stereoselective Hydroelementation of SF5‐Alkynes and Further Functionalizations.

Abstract: Herein is described a fully regio‐ and stereoselective hydroelementation reaction of SF5‐alkynes with N, O and S‐nucleophiles and further functionalization of the corresponding Z‐(hetero)vinyl‐SF5 intermediates, a suitable platform to access α‐SF5 ketones and esters, β‐SF5 amines and alcohols under mild reaction conditions. Experimental and computational comparative studies between SF5‐ and CF3‐alkynes have been performed to highlight and explain the difference of reactivity and selectivity observed between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 94 publications
0
14
0
Order By: Relevance
“…The difference in energy between the distorted fragment and optimized ground‐state geometry is the strain (or distortion) energy ( E strain ). The difference between the activation energy (Δ E ≠ ) and total strain energy corresponds to the interaction energy ( E int ), which has a negative value and counteracts the strain energy [21] . We found that the Δ E int term for the processes involving TS‐ Z and TS‐ E are nearly identical, but they differ in the Δ E strain (Figure 4b).…”
Section: Resultsmentioning
confidence: 91%
“…The difference in energy between the distorted fragment and optimized ground‐state geometry is the strain (or distortion) energy ( E strain ). The difference between the activation energy (Δ E ≠ ) and total strain energy corresponds to the interaction energy ( E int ), which has a negative value and counteracts the strain energy [21] . We found that the Δ E int term for the processes involving TS‐ Z and TS‐ E are nearly identical, but they differ in the Δ E strain (Figure 4b).…”
Section: Resultsmentioning
confidence: 91%
“…Yield of isolated product (the number in parentheses refers to calculated yield by 19 F NMR using PhSCF 3 as internal standard). References of methods: A, 13,21,16 available and difficult to prepare. 36 With our present method, triisopropylsilyl-acetylene 1z delivered 2z in a modest 13% isolated yield, while we obtained a quantitative yield of 2aa featuring a triethylsilyl group.…”
mentioning
confidence: 99%
“…(A) Applications of SF 5 -alkynes in (a) Gold-catalyzed hydration, (b) Gold-catalyzed hydrofluorination, (c) Hydroelementation, (d) Intramolecular amination, (e) Diels–Alder reaction, (f, g) Pyrrole syntheses, , (h) Isoxazoline synthesis, (i) Isoxazole synthesis . (B) Synthesis of SF 5 -alkynes from SF 5 Cl and terminal alkynes.…”
mentioning
confidence: 99%
See 2 more Smart Citations